2020
DOI: 10.1007/s00248-020-01583-w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Regional Oceanography and Hydrothermal Activity on Protist Diversity and Community Structure in the Okinawa Trough

Abstract: Protist diversity and biogeography in the Okinawa Trough 2 Microbial eukaryotes (protists) contribute substantially to ecological functioning in marine ecosystems, but the relative importance of factors shaping protist diversity, such as environmental selection and dispersal, remain difficult to parse. Water masses of a back-arc basin with hydrothermal activity provide a unique opportunity for studying the effects of dispersal and environmental selection on protist communities. In this study, we used metabarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 88 publications
1
14
0
1
Order By: Relevance
“…The Oligohymenophorea and Spirotrichea classes were particularly enriched within Gorda vent fluids (Figures 2, 3), and species within these groups may be specially suited to thrive within the vent environment. For example, scuticociliates (a subclass within Oligohymenophorea; Table S5) have been found previously near hydrothermal vent sites (28, 32), and in addition to their heterotrophic capabilities, are known to be parasitic or to host endosymbionts (31). Ciliates found only within the vent fluid samples, such as Karyorelictea, Plagiopylea, and Euplotia , include species capable of thriving in low oxygen to suboxic environments with modified mitochondria (hydrogenosomes).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Oligohymenophorea and Spirotrichea classes were particularly enriched within Gorda vent fluids (Figures 2, 3), and species within these groups may be specially suited to thrive within the vent environment. For example, scuticociliates (a subclass within Oligohymenophorea; Table S5) have been found previously near hydrothermal vent sites (28, 32), and in addition to their heterotrophic capabilities, are known to be parasitic or to host endosymbionts (31). Ciliates found only within the vent fluid samples, such as Karyorelictea, Plagiopylea, and Euplotia , include species capable of thriving in low oxygen to suboxic environments with modified mitochondria (hydrogenosomes).…”
Section: Resultsmentioning
confidence: 99%
“…Heterotrophic nanoflagellate members of the stramenopile supergroup were overwhelmingly MArine STramenopiles (MAST, in cosmopolitan and resident populations) or Cafeteriaceae (primarily in the near vent bottom water samples) ( Figure 3); both are recognized as important bacterivores with a global distribution and often found in mesopelagic and deep sea surveys (35)(36)(37). MAST have also been found at higher relative sequence abundances within the Mariana Arc vent ecosystem and hydrothermally influenced water masses within Okinawa Trough (17,28).…”
Section: Protistan Grazers Exert Predation Pressure On Hydrothermal Vmentioning
confidence: 99%
“…The protist community structures of various samples have been analyzed ( e.g. , Brisbin et al , 2020 ; Iniesto et al , 2021 ), and differences among these samples were successfully characterized. A comparison of the bulk structure of an entire protist community is important for understanding structural differences at the large-scale level.…”
mentioning
confidence: 99%
“…Deep sea communities therefore may be relying on metabolic plasticity to exploit a variety of environmental conditions, enabling the occupation of both hydrothermal and non-hydrothermal influenced seawater systems. Protistan groups such as ciliates, stramenopiles, dinoflagellates and radiolarians are also ubiquitous in the deep ocean, and may serve as important vectors for transferring carbon obtained from vent sites to the broader bathypelagic ocean (Olsen et al 2015;Murdock and Juniper 2019;Mars Brisbin et al 2020). However, hydrothermal populations can be genomically distinct from background communities at a fine taxonomic level, which has been observed in vent-influenced protistan communities using amplicon sequence variants (ASVs) (Mars Brisbin et al 2020;Hu et al 2021) and bacterial functional genes (Mino et al 2013(Mino et al , 2017, although this was not observed here using an OTU approach.…”
Section: Microbial Community Composition In Background and Hydrothermally-influenced Seawatermentioning
confidence: 99%
“…Protistan groups such as ciliates, stramenopiles, dinoflagellates and radiolarians are also ubiquitous in the deep ocean, and may serve as important vectors for transferring carbon obtained from vent sites to the broader bathypelagic ocean (Olsen et al 2015;Murdock and Juniper 2019;Mars Brisbin et al 2020). However, hydrothermal populations can be genomically distinct from background communities at a fine taxonomic level, which has been observed in vent-influenced protistan communities using amplicon sequence variants (ASVs) (Mars Brisbin et al 2020;Hu et al 2021) and bacterial functional genes (Mino et al 2013(Mino et al , 2017, although this was not observed here using an OTU approach. Interestingly, disconnects between the amplicon and proteomic datasets were apparent with the 16S rRNA analysis indicating cyanobacteria were one of the most relatively abundant taxa identified even in deep waters (≥ 200 m; Fig.…”
Section: Microbial Community Composition In Background and Hydrothermally-influenced Seawatermentioning
confidence: 99%